Dependence of high frequency properties on concentration of amorphous ferroalloy particle in composites. (July 2014) - Zeng, M.; Liu, J.; Yu, R.; Zhao, D.; Wang, X.
<x content-type="archive" xml:space="preserve">Abstract</x> The amorphous ferroalloy particle was filled into the polymeric matrix. The filler concentration has much effect on the absorption properties of the composites and changes the matching frequency. Bruggeman–Hanai formula was also applied in analysis of the permittivity or the permeability. The reflection loss was calculated from the complex permittivity and complex permeability of the composites. The results indicate that the filler ratio and the thickness had important effect on the absorption properties of the composites, showing that the amorphous ferroalloy particle is one of the suitable candidates to achieve high microwave absorption in GHz range.